EXPLORING ESL STUDENTS’ USE OF MULTIMEDIA IN AN ENGLISH-SPEAKING CLASSROOM - Talitha Segar; Adelina Asmawi (MOJES: Malaysian Online Journal of Educational Sciences, 2024)
This study delves into the utilization of multimedia in English-speaking classrooms among lower secondary students in Malaysia, specifically focusing on form one students, exploring its efficacy and potential constraints. Amidst a global context where English proficiency is increasingly indispensable, traditional teaching methodologies have shown limitations, particularly in non-native English-speaking regions like Malaysia. The investigation adopts a qualitative approach, incorporating semi-structured interviews and classroom observations to offer a comprehensive insight into the interactions between students, teachers, and multimedia tools in learning English speaking skills. The findings reveal that multimedia platforms such as podcasts, speech recognition software, and Prezi significantly enhance student engagement and speaking proficiency. These tools, when used as both teaching and learning aids in speaking lessons, facilitate active group discussions, spontaneous speaking, and independent responses, thereby fostering a more dynamic and interactive learning environment. Students reported increased confidence and fluency in English, attributing these improvements to the diverse and immersive experiences afforded by multimedia learning. However, the study also highlights several challenges associated with integrating multimedia in educational settings, including access, technical limitations, and the digital divide. These obstacles underscore the need for targeted strategies to ensure equitable access to multimedia resources and enhance digital literacy among educators and learners. Conclusively, multimedia represents a potent tool for enhancing English-speaking skills among Malaysian lower secondary students, offering pathways to more engaging and effective language learning experiences. Nevertheless, realizing its full potential necessitates a concerted effort to overcome existing barriers, calling for policy interventions, infrastructure development, and pedagogical innovation to support multimedia integration in language education. This study contributes to the broader discourse on educational technology, advocating for a nuanced approach that leverages the benefits of multimedia while addressing the challenges of digital integration in learning environments.